0464 Patient perspectives on facilitators and barriers to engagement with digital CBT-I. (25th May 2022) - Melikyan, Diana; Santarossa, Sara; Sagong, Chaewon; Sultan, Zain; Drake, Christopher; Cheng, Philip
Abstract: Introduction: Digital Cognitive Behavioral Therapy for Insomnia (dCBT-I) is a highly effective self-guided mHealth treatment for insomnia; however, completion and adherence rates are poor, especially among marginalized individuals. The present study explored facilitators and barriers to engagement with dCBT-I. Methods: Thematic analysis was conducted on qualitative data collected in those who engaged with dCBT-I. A total of 151 written feedback, 34 individual interviews, and 1 focus group of six racial minorities with low socioeconomic status (SES) was used. A combined inductive and deductive approach was utilized, where an initial codebook was developed but emergent codes were also included in the coding process. Consensus between four independent coders were achieved prior to thematic analysis. Results: Thematic analysis revealed five themes: digital person to person component, type and extent of information, users' sense of autonomy, app functionality, and importance of tailored content. Overall, users felt that the dCBT-I content was engaging (e.g., "easily understandable", "well-paced"), and valued the accessibility of a digital treatment (e.g., "I greatly enjoyed the weekly sessions in the privacy of my own home"). Participants across demographic groups felt that the virtual therapist (i.e., "The Prof") increased engagement (e.g., "The Prof was entertaining", "The Prof has a great voice…educated and soothing without condescension").Barriers to engagement, particularly in those with lower SES, included eHealth literacy (e.g., "I had issues filling out my sleep diary") and a desire for more human contact (e.g., "I maybe would have liked more communication throughout, maybe just checking in once to see if things were okay"). There was strong consensus among non-completers that additional support would have prevented treatment dropout (e.g., "HELP button or someone you could've asked questions"). Others expressed concerns about the lack of tailoring to their specific circumstances (e.g., "this system does not take into consideration 'physical' causes of my sleep problems"). Conclusion: Although dCBT-I has high accessibility and scalability, those with lower health literacy may experience lower self-efficacy and negative outcome expectancy as barriers to treatment engagement and completion. There is support that enhancing dCBT-I with personalized support and tailored content may improve treatment adherence and completion. Support (If Any): K23HL136188; R01HL159180